2020
DOI: 10.3390/cancers12092471
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Studies Applying Cytokine-Induced Killer Cells for the Treatment of Renal Cell Carcinoma

Abstract: There is growing interest in cytokine-induced killer (CIK) cells on the integrated therapy of patients with RCC, especially those in the late stage or refractory to conventional chemotherapy and radiotherapy. In this review, a total of 15 clinical studies including 681 patients enrolled in CIK cell immunotherapy were outlined. Three-hundred-and-eighty-two patients with RCC were treated with CIK cells alone or in combination with DC vaccination, targeted agents sunitinib or sorafenib, and the PD-1 inhibitor pem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…TIGIT–CD155 signaling was also observed in cytokine-induced killer (CIK) cells expressing CD3 and CD56 molecules ( 101 , 102 ). As observed indirectly by Zhang et al., who analyzed the literature concerning the clinical trial ongoing on renal cell carcinoma patients enrolled in integrated CIK cell immunotherapy, the TIGIT blocked enhanced CIK proliferation and the release of pro-inflammatory cytokines, such as IFN-γ, IL-6, and TNF-α ( 102 ).…”
Section: Tigit Pathways and Immune Cells Involvedmentioning
confidence: 99%
“…TIGIT–CD155 signaling was also observed in cytokine-induced killer (CIK) cells expressing CD3 and CD56 molecules ( 101 , 102 ). As observed indirectly by Zhang et al., who analyzed the literature concerning the clinical trial ongoing on renal cell carcinoma patients enrolled in integrated CIK cell immunotherapy, the TIGIT blocked enhanced CIK proliferation and the release of pro-inflammatory cytokines, such as IFN-γ, IL-6, and TNF-α ( 102 ).…”
Section: Tigit Pathways and Immune Cells Involvedmentioning
confidence: 99%
“… 1 The EUA Guidelines suggested that surgery is the only curative treatment for localized renal cell carcinoma (RCC). 2 , 3 The partial nephrectomy (PN) and radical nephrectomy (RN) for patients with ccRCC larger than 7 cm exhibited equivalent oncologic outcomes. 4 Basing on quality-of-life and oncological outcomes, localized cT1 carcinomas are best treated through nephron-sparing surgery (NSS) rather than RN.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the relative contribution of several immunotherapeutic approaches has helped to partially tackle this adverse effect of disease in the clinics. Among these approaches, cytokine-induced killer (CIK) cell therapy has played a pivotal role and raised the bar regarding treatment response due to its safe and efficient methodology [ 22 , 23 , 24 ]. The uniqueness of CIK cells is their encouraging synergetic effect with cancer associated inhibitors/compounds in preclinical models since cannabinoids have been the subject of intensive cancer research, in particular cannabinoid receptor 2 (CB2) due to its expression in cells of the immune system where CIK cells also play an important role.…”
Section: Discussionmentioning
confidence: 99%